Feedback strategies for visual search in airframe structural inspection - Gramopadhye, Anand K.; Drury, Colin G.; Sharit, Joseph (International journal of industrial ergonomics, 1997)
Feedback of information has consistently shown positive results in human inspection, provided it is given in a timely and appropriate manner. Feedback serves as the basis of most training schemes; traditionally this has been performance feedback. Other forms of feedback which provide strategy information rather than performance information may have a role in improving inspection. This study compared performance feedback and cognitive feedback in a realistic simulation of an aircraft structural inspection task. Performance (time, errors) feedback showed the greatest improvements in performance measures. Cognitive feedback enhanced efficiency measures of search strategy. When cognitive feedback consisted of visual representations of the path and the coverage of the search sequence, subjects also were able to use this task information to improve their search performance. Relevance to industry The results of this study have direct implications on developing training strategies for improving industrial inspection performance. The results can be used to design superior training programs to improve airframe inspection and thus aviation safety. The results also can be extended to complex inspection tasks in other industries (printed circuit board inspection in the electronic industry, cloth inspection in the textile industry, inspection of food products in the agricultural industry and in-process inspection in manufacturing industry).